Adekvatnoe pitanie dlja doškol'nikov - sportsmenov - Ivanova, L. A.; Kazakova, O. A.; Nenasheva, E. V.; Popova, T. N.; Kalinina, T. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article presents the data from the survey of the educators and parents of the preschool children of two kindergartens No. 378 and 61 of Samara, the purpose of which is to identify the nature of the nutrition of preschoolers in modern conditions, both at the preschool and at home (daily allowance), engaged in sports sections. We have studied the number of meals, the main sources of nutrients, preferences in the diet of preschoolers, contraindications and age limits of the subjects. The authors of the article found that many children, already at preschool age, are intensely involved in sports feel lack of the sufficient nutritional nutrients, which, in its turn, negatively affects their actual and mental development.